Investigation of systemic immune-inflammation index, neutrophil/high-density lipoprotein ratio, lymphocyte/high-density lipoprotein ratio, and monocyte/high-density lipoprotein ratio as indicators of inflammation in patients with schizophrenia and bipolar disorder - Wei, Yanyan; Wang, Tingting; Li, Guoguang; Feng, Junhui; Deng, Lianbang; Xu, Haiting; Yin, Lu; Ma, Jinbao; Chen, Dongning; Chen, Jingxu (Frontiers in Psychiatry, 2022)
Background: The systemic immune-inflammation index (SII), system inflammation response index (SIRI), neutrophil/ high-density lipoprotein (HDL) ratio (NHR), lymphocyte/ HDL ratio (LHR), monocyte/ HDL (MHR) ratio, and platelet/ HDL ratio (PHR) have been recently investigated as new instruments for giving notice inflammation. The purpose of the research is to use large-scale clinical data to discuss and compare the predictive ability of the SII, SIRI, NHR, LHR, MHR and PHR in patients with SCZ and BD, to investigate potential biomarkers. Methods: In this retrospective, naturalistic, cross-sectional study, we collected the hematological parameters data of 13,329 patients with SCZ , 4,061 patients with BD manic episodes (BD-M) and 1,944 patients with BD depressive episodes (BD-D). 5,810 healthy subjects served as the healthy control group (HC). The differences in the SII, SIRI, NHR, LHR, MHR, PHR were analyzed, and a receiver operating characteristic (ROC) curve was used to analyze the diagnostic potential of these parameters. Results: Compared with HC, the values of SII, SIRI, NHR, LHR, MHR, PHR and the levels of neutrophil, monocyte, triglycerides (TG) were higher in SCZ and BD groups, and levels of platelet, cholesterol (CHO), HDL, low density lipoprotein (LDL), apoprotein B (Apo B) were lower in SCZ and BD groups. Compared to the BD group, the values of the SIRI, lymphocyte, monocyte and HDL were lower in SCZ group, and values of SII, NHR, PHR and platelet were higher in SCZ group. In contrast with BD-D group, the values of SII, SIRI, NHR, MHR, and levels of neutrophil, monocyte, platelet were higher in BD-M, and the levels of CHO, TG, LDL and Apo B were lower in BD-M. MHR and NHR were predictors for differentiating SCZ from HC, the SIRI, NHR and MHR were predictors for differentiating BD-M from HC, the MHR was predictors for differentiating BD-D from HC, the combination model of the indicators improved diagnostic effectiveness. Conclusions: Our study highlights the role of systemic inflammation in the pathophysiology of SCZ, BD-M and BD-D, and the association between inflammation and lipid metabolism, these inflammation and lipid metabolism indicators showed different variation patterns in SCZ, BD-D and BD-M.